2016
DOI: 10.1118/1.4957157
|View full text |Cite
|
Sign up to set email alerts
|

MO‐AB‐BRA‐05: [18F]NaF PET/CT Imaging Biomarkers in Metastatic Prostate Cancer

Abstract: Purpose: Clinical use of 18F‐Sodium Fluoride (NaF) PET/CT in metastatic settings often lacks technology to quantitatively measure full disease dynamics due to high tumor burden. This study assesses radiomics‐based extraction of NaF PET/CT measures, including global metrics of overall burden and local metrics of disease heterogeneity, in metastatic prostate cancer for correlation to clinical outcomes. Methods: Fifty‐six metastatic Castrate‐Resistant Prostate Cancer (mCRPC) patients had NaF PET/CT scans performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Therefore, the theory of polyclonal seeding strongly supports heterogeneity between metastases, which results in heterogeneous treatment response. Indeed, heterogeneous treatment response between patients and between metastases has been reported (Gundem et al 2015, Hong et al 2015, Harmon et al 2016, Morin et al 2017, Nakazawa et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, the theory of polyclonal seeding strongly supports heterogeneity between metastases, which results in heterogeneous treatment response. Indeed, heterogeneous treatment response between patients and between metastases has been reported (Gundem et al 2015, Hong et al 2015, Harmon et al 2016, Morin et al 2017, Nakazawa et al 2017.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, treatment response is based on measurement of functional and anatomical changes of metastases. Therefore, molecular imaging modalities such as positron-emission tomography (PET), enabling visualization of the mentioned changes, can be successfully used to assess treatment response (Soussan et al 2014, Liu et al 2015, Simoncic et al 2015, Apolo et al 2016, Harmon et al 2016, Morin et al 2017. With quantitative analysis of parametric images, different imaging metrics can be extracted from PET scans, some of which have been shown to be strong predictors of disease progression and patient outcome (Cook et al 2015, Li et al 2017.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…NaF PET/CT additionally provides robust quantitative assessment of tumor burden, which has been shown to relate to clinical outcome, either for progression-free survival (Harmon et al 2017) or overall survival (Lindgren Belal et al 2017). Furthermore, Harmon et al showed that the heterogeneity of responses of individual lesions is highly predictive of progression-free survival, which motivates further assessment of individual lesions (Harmon et al 2016).…”
Section: Introductionmentioning
confidence: 99%